Socialization of Strategies for Building MSME Businesses by Following Digitalization Promotion Trends in a Village - Primadi Candra Susanto; Olfebri Olfebri; Aang Gunawan; Basri Fahriza; Reza Fauzi Jaya Sakti; Agus Suhendra; Alfais Amin Darmawan; Rohana Sitanggang (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Micro,Small, and Medium Enterprises (MSMEs) are a vital pillar of the national economy, significantly contributing to employment, innovation, and regional economic development. However, in the ever-evolving digital era, many MSMEs have yet to optimally utilize digital promotional technologies and trends, leading to limited market reach and business growth. This community service activity aims to improve MSMEs' understanding and skills in building and developing their businesses through digital-based promotional strategies. The methods used in this activity include interactive outreach, hands-on training, and mentoring focused on the use of social media, online marketplaces, and other relevant digital platforms. The activity was conducted in collaboration with the MSME community using a participatory approach, enabling participants to actively engage in learning and directly apply the materials provided. The results of the activity indicate that participants showed a significant increase in knowledge and awareness regarding the importance of digital branding, designing attractive and effective promotional content, and utilizing various digital tools to expand market access. Additionally, many participants expressed greater confidence in managing digital platforms to promote their products and services independently. This increase in digital literacy is crucial in helping MSMEs remain competitive and adaptive to market changes brought about by technological advances. By equipping MSMEs with relevant digital promotion skills, this initiative contributes to the broader goal of supporting the growth of resilient, sustainable, and innovative small businesses. In the long term, such community-based empowerment efforts are expected to foster economic resilience and inclusiveness in the face of ongoing digital economic transformation.